Performance evaluation of biodegradable metalworking fluids for machining process - Talib, Norfazillah (2017)
The widely use of metalworking fluids (MWFs) petroleum-based in the industry have a negative impact to the environment and human. Thus, various initiatives have been undertaken to develop bio-based MWFs especially from crude jatropha oil (CJO). However, the main drawback of CJO is that it has low thermal-oxidative stability. Therefore, the objective of this study is to develop a new formulation of CJO-based MWFs. The newly developed modified jatropha oils (MJOs) were formulated using transesterification process at various molar ratios of jatropha methyl ester to trimethylolpropane (JME:TMP) denoted by MJO1 (3.1:1), MJO3 (3.3:1) and MJO5 (3.5:1). Later, the MJOs were blended with hexagonal boron nitride (hBN) particles at various concentrations (0.05 to 0.5wt.%). MJOs with and without hBN particles were analysed based on the physicochemical properties, tribology behaviour test, orthogonal cutting and turning proses. From the results, MJO5 showed an improvement at thermal (high viscosity index) and oxidative stability (lubricant storage). MJO5c (MJO5+0.5wt.% of hBN particles) showed the optimum physicochemical properties. In the contrary, MJO5a (MJO5+0.05wt.% of hBN particles) exhibited excellent tribological behaviour as reduction of friction and wear, with high tapping torque efficiency. In the orthogonal cutting process, MJO5a recorded the lowest machining force and temperature, thus contributed to the formation of thinner chips, small tool-chip contact length and reduction of the specific energy. MJO5a produced an excellent result in the machinability test by reducing the cutting force, cutting temperature and surface roughness stimulated longer tool life and less tool wear. In conclusion, the MJO5a has a potential impact on the lubricant market as a sustainable MWFs for the machining processes.